Cobre e zinco no solo: crescimento e parâmetros fisiológicos em videiras jovens e aveia preta - Tiecher, Tadeu Luis (2017)
The Campanha Gaúcha is one of the main wine regions of Brazil that suffers from climatic factors favorable to the development of fungal diseases on the leafs of the grapevine (Vitis vinifera). Generally, the control of these diseases is carried out with successive applications of copper-based (Cu) fungicides, such as the Bordeaux mixture, which generates Cu accumulation in the soil up to toxic levels for the vines and the plants that co-inhabit the vineyards, such as black oats (Avena strigosa Schreb.). In the vineyards of the Campanha Gaúcha, the Cu toxicity to plants is observed at relatively low Cu-levels in the soil, compared to other wine growing regions of the world, due to the characteristics of the soils from this region, that are generally sandy, acidic and have low soil organic matter (SOM) content. In order to reduce the amount of Cu applied in the vineyards, Zn-based fungicides have been used as an alternative to replace the Bordeaux mixture that have zinc (Zn) in its formulation. As the number of fungicide applications is still high, a quick increase in soil Zn content has been observed in vineyard soils that already have a high Cu content. Therefore, the objective of this Thesis was to evaluate the effect of the combination of Cu and Zn levels on a sandy soil from the Campanha Gaúcha on the growth, physiological status and the morphological changes in the root system of young grapevines and black oats. For that, three studies were carried out under greenhouse conditions using a Typic Hapludalf soil, with 5.4 % of clay and 0.9% of SOM. Studies I and II were carried out in pots containing 4.0 kg of soil, with black oats plants (30 days of cultivation) and young grapevines (60 days of cultivation), respectively, and treatments consisted of 0, 30 and 60 mg Cu kg-1 combined with the addition of 0, 15, 30, 60, 120 and 180 mg Zn kg-1. Study III was carried out in Rizobox-type containers, containing 2.4 kg of soil, with young grapevines (60 days of cultivation) and the treatments were 0 and 120 mg Cu kg-1 combined with 0, 120 and 240 mg Zn kg-1. In studies I and II, it was determined the accumulation of dry matter in the roots and shoots, Cu and Zn contents in the roots and shoots and the translocation of these metals from the roots to shoots, the chlorophyll a fluorescence, the photosynthetic pigments and the activity of antioxidant enzymes. In study III, in addition to these analyses, the root morphology and gas exchanges performed by plants were also evaluated. In all studies, young grapevines and black oats showed retention of Cu and Zn in their roots, reducing the translocation to the shoots. However, at the highest Cu and Zn doses of all the studies, it was observed decreased plant growth and photochemical efficiency was associated to the decrease of the content of photosynthetic pigments. In addition, changes in gas exchange and root system of young vines were observed in study III. In all the studies, activity of the antioxidant enzymes was higher in intermediate doses of Zn, indicating the activation of the antioxidant system. However, stressful conditions in with high levels of Cu and Zn was not reversed. This way, although the Zn levels currently observed under field conditions in the Campanha Gaúcha are still at levels lower than those that presented risk of toxicity to the plants, the sandy soils of vineyards from this region that are already contaminated with Cu may have their toxic effect on young grapevines and black oat plants potentiated as the soil Zn content increases. In order to decrease the phytotoxic potential of Cu and Zn in sandy soils from the Campanha Gaúcha vineyards, it is imperative to use management practices that aim to increase the adsorption capacity of these metals in the soil and decrease the addition of Cu and Zn. This can only be possible by using soil management that allows to increase the SOM content and to maintain soil pH close to the ideal for vines (6.0), besides using preventive strategies to control plant diseases, rotation of active principles and, especially, modes of action of fungicides.